Word Formative Derivation in Russian-Language Social Networks - Asatryan, Kristine (Bulletin of Yerevan University H: Russian Philology, 2023)
The article considers the processes of word formation derivation, particularly the affixation, which is actively and vividly manifested in the Russian-speaking cyberspace. With the development of the Internet new phenomena, concepts and subjects that need to be nominated appear. The vocabulary of the language of Internet communication is replenished not only by borrowings, but also due to the word production process.The Russian language has a developed derivational system, the vocabulary is constantly developing and replenishing. One of the most common ways of forming new words in the Internet space is the affixal word formation. Based on the analysis of the most frequently used lexical units in social networks, the main methods of affixal derivation are revealed, when a new word is formed by adding a prefix or suffix to an already existing borrowing.Prefixes and suffixes that are added to derived foreign-language roots play an important role in determining the partial affiliation of derivatives. The affixes themselves are divided into substantive, adjectival, adverbial and verbial, according to which the lexico-grammatical category the derivatives formed by affixation belong to.The nominations of acts and attributes are most actively produced, but in cases with nominations of objects and phenomena, we mainly deal with borrowings. The prefixation is more common for verbs, while the suffixation has become widespread in the formation of nouns, adjectives and adverbs. Such methods of word formation (based on borrowed roots) become the dominant sources of replenishment and enrichment of the vocabulary of the modern Russian language.
Keywords: internet discourse; social network; substantive derivation; adjectival derivation; adverbial derivation; verbial derivation; affixation; diminutive